Fundamental investigation of stress corrosion cracking of E690 steel in simulated marine thin electrolyte layer. (March 2019) - Liu, Z.Y.; Hao, W.K.; Wu, W.; Luo, H.; Li, X.G.
Highlights: An in-situ mechanical-electrochemical test system was established to investigate the SCC mechanism of E690 steel in a marine TEL. A critical oxygen concentration, approximately 21% by volume, was found to give rise to the highest susceptibility of E690 to SCC. Hydrogen oxidation catalyzed by ferric ion was demonstrated to reduce the SCC sensitivity. Abstract: The mechanism of stress corrosion cracking (SCC) of E690 high-strength steel in a marine thin electrolyte layer (TEL) was investigated by performing in-situ mechanical–electrochemical tests, slow strain rate tensile (SSRT) tests, and characterization of corrosion morphology. It was concluded that E690 steel was highly sensitive to SCC, which was jointly determined by local anodic dissolution (AD) and hydrogen embrittlement (HE) both caused by dissolved O2 . In addition to these functions, hydrogen oxidation catalyzed by ferric ion was found. There was a critical oxygen concentration, approximately 21% by volume, between these two different roles. Below this value, the increase in the oxygen concentration promoted the synergistic effect of AD and HE, resulting in the increase in SCC susceptibility. However, above this value, worse general corrosion offset crack initiation as well as the oxidation of hydrogen catalyzed by ferric ions reduced the SCC susceptibility.